Exploring Higher Education Students' Self-Efficacy: How Self-Efficacy Dimensions Influence Numeracy - Herra Aprillia Sabrina; Yoppy Wahyu Purnomo; Fery Muhamad Firdaus; Danuri (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2024)
Numeracy is associated with students' self-efficacy, and it is crucial to examine the elements affecting numeracy proficiency, particularly behavior, including self-efficacy. A lack of research amalgamates both dimensions, encompassing the reciprocal impacts and the impact of contextual factors like gender and educational background. This study seeks to ascertain the influence of mathematics self-efficacy aspects on numeracy among elementary school teacher education students in the Yogyakarta region. The sampling method employed was non-probability sampling, specifically utilizing a convenience sampling methodology with a sample size of 215. The data analysis employed Structural Equation Modeling – Partial Least Squares (SEM–PLS). This study identifies the "strength" dimension of self-efficacy in numeracy as the most influential factor affecting an individual's numeracy skills. Frequent exposure to consistent and relevant learning experiences enhances students' confidence in decision-making when confronted with numeracy challenges. The "strength" of students' mathematics self-efficacy can be affected by various aspects, such as pleasant learning experiences, social support, and achievements in solving mathematical obstacles. Students who frequently confront and successfully resolve mathematical issues experience increased confidence as they trust in their capacity to tackle analogous tasks in the future. If this conduct is consistently exhibited during the student's study period, the numeracy component may enhance and serve as a valuable resource for future teachers.